Cognitive Deficits, Apathy, and Hypersomnolence Represent the Core Brain Symptoms of Adult-Onset Myotonic Dystrophy Type 1 - Miller, Jacob N.; Kruger, Alison; Moser, David J.; Gutmann, Laurie; van der Plas, Ellen; Koscik, Timothy R.; Cumming, Sarah A.; Monckton, Darren G.; Nopoulos, Peggy C. (Frontiers in Neurology, 2021)
Myotonic dystrophy type 1 is the most common form of muscular dystrophy in adults, and is primarily characterized by muscle weakness and myotonia, yet some of the most disabling symptoms of the disease are cognitive and behavioral. Here we evaluated several of these non-motor symptoms from a cross-sectional time-point in one of the largest longitudinal studies to date, including full-scale intelligence quotient, depression, anxiety, apathy, sleep, and cerebral white matter fractional anisotropy in a group of 39 adult-onset myotonic dystrophy type 1 participants (27 female) compared to 79 unaffected control participants (46 female). We show that intelligence quotient was significantly associated with depression (P < 0.0001) and anxiety (P = 0.018), but not apathy (P < 0.058) or hypersomnolence (P = 0.266) in the DM1 group. When controlling for intelligence quotient, cerebral white matter fractional anisotropy was significantly associated with apathy (P = 0.042) and hypersomnolence (P = 0.034), but not depression (P = 0.679) or anxiety (P = 0.731) in the myotonic dystrophy type 1 group. Finally, we found that disease duration was significantly associated with apathy (P < 0.0001), hypersomnolence (P < 0.001), IQ (P = 0.038), and cerebral white matter fractional anisotropy (P < 0.001), but not depression (P = 0.271) or anxiety (P = 0.508). Our results support the hypothesis that cognitive deficits, hypersomnolence, and apathy, are due to the underlying neuropathology of myotonic dystrophy type 1, as measured by cerebral white matter fractional anisotropy and disease duration. Whereas elevated symptoms of depression and anxiety in myotonic dystrophy type 1 are secondary to the physical symptoms and the emotional stress of coping with a chronic and debilitating disease. Results from this work contribute to a better understanding of disease neuropathology and represent important therapeutic targets for clinical trials.